Traditional food and healthy diet: The Mediterranean diet example - Troncoso-Pantoja, Claudia (2019)
The necessity for taking actions that strengthen activities intended for health promotion and disease prevention has allowed the rediscovery of traditional dishes as an option for healthy diet. Traditional dishes not only gather dietary and nutritional aspects, but also social and cultural elements associated with a culinary dish, all of which enrich and give identity to people, families and communities. This review theorizes and reflects on the relationship between traditional dishes and healthy diet based on one of the most well-known dietary patterns worldwide: the Mediterranean diet. This feeding regime allows the rendezvous between healthy food and culinary preparations, promotes a lifestyle that prevents the onset of chronic diseases, and has a sociocultural connotation based on its designation as culinary heritage of humanity, which gives identity to the Mediterranean nations. This article presents the characteristics of such feeding regime and its classic application as a healthy diet. It also goes more deeply into its role as part of the cultural intangible heritage of humanity, as well as its current application and representation as a healthy and sustainable diet, and poses the need for recognizing traditional dishes as an opportunity for healthy diet.